Detailed neuropathologic report of COVID-19 complicated by large intracerebral hemorrhage and periventricular lesions with macrophagic infiltrates - Levine, Adrian; Lee, Carol; Fava, Craig; Tsang, Frankie; McNeil, Kelly; Yip, Stephen T.; Hirsch-Reinshagen, Veronica (Free Neuropathology, 2021)
Infection with the SARS-CoV-2 virus affects a wide range of systems. Significant involvement of the central nervous system has been described, including ischemic and hemorrhagic strokes. Thus far, neuropathologic reports of patients who passed away from COVID-19 have generally described non-specific findings, such as variable reactive gliosis and meningeal chronic inflammatory infiltrates, as well as the consequences of the infection’s systemic complications on the brain, including ischemic infarcts and hypoxic/ischemic encephalopathy. The neuropathological changes in patients with COVID-19 and large hemorrhagic strokes have not been described in detail. We report the case of an elderly male who had a long course of COVID-19 and ultimately passed away from a large intracerebral hemorrhage. In addition to acute hemorrhage, neuropathologic examination demonstrated non-specific reactive changes and chronic periventricular lesions with macrophagic and perivascular lymphocytic infiltrates without evidence of demyelination or presence of SARS-CoV-2 by PCR test. This manuscript expands the spectrum of reported neuropathological changes in patients with COVID-19.